Do state funding, geographic location, and networks matter?: The case of prominent Irish actors, directors and writers. Issue 2 (14th March 2020) - O'Hagan, John; Murphy, Denis; Barton, Ruth
ABSTRACT: Using a uniquely constructed data set, we look at the ecologies of creative careers in film/TV-drama/theatre, using a detailed interview questionnaire case study of eighty-two prominent workers in the Irish film/TV-drama/theatre sectors. Three influences on career progression are given special attention: state patronage, geographic location and networks. There is strong evidence to show that those interviewed consider state patronage as very important to their career development, particularly in relation to "breakthrough" events. Even this group depends on outside work, particularly in advertising, to supplement incomes. Our findings confirm that prominent creative workers tend to be geographically concentrated and consider such proximity to other creative workers as important. A very large proportion of them also consider networks/personal connections as very important to career success, in terms of three main advantages: work/job contacts, the generation of new ideas and moral support/understanding.